Rosai Dorfman disease diagnosed by fine-needle aspiration cytology in a young man with HIV infection - Sall, Abibatou (John Wiley & Sons, Ltd, 2015)
RDD (Rosai Dorfman disease) is a rare and benign histiocytic proliferative disorder of unknown etiology. FNAC (Fine-needle aspiration cytology) is a useful and reliable tool for the diagnosis of RDD, and as such, biopsy is avoidable.